Water Runoff, sediment transport and related impacts in the Southeastern Black Sea rivers - Berkun, Mehmet; Aras, Egemen; Özel Akdemir, Ümmükülsüm (Gh Asachi Technical Univ Iasi, 71 Mangeron Blvd, Iasi, 700050, Romania, 2015)
The Southeastern Black Sea coastal region in Turkey and Georgia is under threat of severe coastal erosion and shoreline recession. The main reason for this problem is the response of the coast to human activities. While water discharge rates were reduced by dams by approximately 7% only, about 98% of the suspended sediment is being captured by the dams, leading to reservoir siltation over time in the southern Black Sea Region Rivers in Turkey. About 83% of the total suspended sediments are carried by the Coruh River to its mouth, which determines the characteristics of the river and the shape of the coastal region. In this study, the effect of water runoff and sediment transport to the Black Sea Coast was investigated.
Keywords: Black Sea; Coastal erosion; Coruh river; Dams; Environmental effect; River runoff; Sediment load; Heavy-metals; Catchment; Discharge; Dynamics; Erosion; Turkey